Technique for Differentiating Particles That Are Cell-Associated or Ingested by Macrophages - Gardner, Donald E. (1973)
Phagocytosis is a two-step process involving attachment and ingestion of particulate material. It is often difficult to determine under a light microscope whether the particles are actually ingested or are merely attached to the cell. A more accurate, easy to perform technique with the use of xylene has been developed for determining the difference between the attachment and ingestion of polystyrene latex spheres. The xylene treatment dissolves the extracellular spheres, leaving only the intracellular spheres to be counted by the experimenter to obtain a more accurate phagocytic index. This technique also allows an investigator to get an ingestion index, an attachment index, or both.